Patterns of diversity in biomedical coauthorships: An analysis across authors’ ethnicity, gender, age, and expertise - Mishra, Apratim; Lee, Haejin; Jeoung, Sullam; Torvik, Vetle I.; Diesner, Jana (PloS one, 2025)
Multiple studies have linked diversity in scientific collaborations to innovative and impactful research. Here, we explore how different diversity indices—ethnicity, gender, academic age, and topical expertise—interact and thereby influence scientific impact. Leveraging nearly 900,000 biomedical journal articles from PubMed, published in major journals between 1991 and 2014, we investigate the nuanced relationships among these diversity indices and their collective influence on research outcomes. By systematically varying model parametrizations, we assess the robustness of the observed relationships and examine multiple methodological choices. Our findings reveal a consistent pattern of demographic homophily, where scientists tend to collaborate with others who share similar ethnic and gender backgrounds. While each diversity index correlates significantly with impact when considered individually, gender diversity and topical expertise emerge as the strongest positive predictors of impact after accounting for key covariates. However, the association between diversity and impact is moderated by the number of collaborating authors, with larger teams sometimes showing opposite trends due to interactions between the computed diversity indices and team size. Despite this complexity, the practical drivers of scientific impact for an article remain the journal of publication, authors’ prior citation rate, and the number of co-authors. On further examining expertise diversity through three separate dimensions: variety, balance, and disparity, our findings indicate that impactful teams balance a wide range of subject matter expertise while maintaining a focused connection on closely related topics. These findings highlight the importance of strategic team composition and underline the significance of team diversity in scientific research.